The Criminalization of Compliance - Haugh, Todd (2017)
Corporate compliance is becoming increasingly “criminalized.” What began as a means of industry self-regulation has morphed into a multi-billion-dollar effort to avoid government intervention in business, specifically criminal and quasi-criminal investigations and prosecutions. In order to avoid application of the criminal law, companies have adopted compliance programs that are motivated by and mimic that law, using the precepts of criminal legislation, enforcement, and adjudication to advance their compliance goals. This approach to compliance is inherently flawed, however—it can never be fully effective in abating corporate wrongdoing. Criminalized compliance regimes are inherently ineffective because they impose unintended behavioral consequences on corporate employees. Employees subject to criminalized compliance have greater opportunities to rationalize their future unethical or illegal behavior. Rationalizations are a key component in the psychological process necessary for the commission of corporate crime—they allow offenders to square their self-perception as “good people” with the illegal behavior they are contemplating, thereby allowing the behavior to go forward. Criminalized compliance regimes fuel these rationalizations, and in turn, bad corporate conduct. By importing into the corporation many of the criminal law’s delegitimizing features, criminalized compliance creates space for rationalizations, facilitating the necessary precursors to the commission of white collar and corporate crime. The result is that many compliance programs, by mimicking the criminal law in hopes of reducing employee misconduct, are actually fostering it. This insight, which offers a new way of conceptualizing corporate compliance, explains the ineffectiveness of many compliance programs and also suggests how companies might go about fixing them